Reverberations of Dharmakīrti's Philosophy: Proceedings of the Fifth International Dharmakīrti Conference Heidelberg August 26 to 30, 2014 (Verlag der Österreichischen Akademie der Wissenschaften, 2020)
This proceedings volume contains 30 papers dealing with the history, literature and ideas of the logico-epistemological school of Indian Buddhism initiated by Dignaga and Dharmakirti, and related currents in South Asia (India), Tibet and East Asia (China). The papers address historical and philological problems raised by important recent manuscript discoveries, pursue specific research questions in the history of philosophy, and undertake philosophical reconstructions and critical examinations relating to individual theories and arguments. By focusing on philosophical currents in Asia that developed and applied rigorous philosophical methods, the volume also aims to contribute to the formation of a better-founded global historical awareness in the field of philosophy.